Granulomatosis with polyangiitis: Experience of 42 patients from a single-center, tertiary care hospital in Mumbai - Sunilkumar Rajmani Singh; Jyotsna Oak; Mahin Salim Olickal (Indian Journal of Rheumatology)
Background: There is a paucity of data on granulomatosis with polyangiitis (GPA) from western India. The present study describes the clinical manifestations, treatment, and outcome of 42 patients from a single-center, tertiary care hospital in Mumbai. Methods: This is a retrospective observational study. From our database, patients with a diagnosis of GPA over a 10-year period (January 2010 to December 2019) were included in the study. Clinical manifestations, laboratory features, Birmingham Vasculitis Activity Score (BVAS-v3), treatment, and outcomes were analyzed. Results: Forty-two patients with GPA were identified. The median age was 48.5 years with an equal number (n = 21) of males and females. Localized, early systemic, generalized, severe, and refractory disease was seen in 4, 11, 15, 8, and 4 patients, respectively. Pulmonary manifestations (n = 27) were most common at presentation followed by renal (n = 21) and ear, nose, and throat (ENT) (n = 20). Ocular and articular disease was seen in 11 patients each. Cutaneous (n = 8) and nervous system (n = 6) involvement was less common. Unusual manifestations included suburethral mass, prostatitis, and pancreatitis. The median BVAS v3 was 14.5. Rituximab was used in 12 patients and achieved remission in 9 patients. The median duration of follow-up was 36 months. Three patients expired. Relapse of disease occurred in 17 patients. Ten patients had episodes of severe infection. No malignancy was observed. Conclusion: GPA in western India has a similar clinical profile to other parts of the country. Pulmonary, ENT, and renal involvement is common. Relapse rates are high. Rituximab is an effective therapy for severe, relapsing, or refractory disease.